High-resolution FLAIR MRI at 7 Tesla for treatment planning in glioblastoma patients. (January 2019) - Regnery, Sebastian; Knowles, Benjamin R.; Paech, Daniel; Behl, Nicolas; Meissner, Jan-Eric; Windisch, Paul; Ben Harrabi, Semi; Bernhardt, Denise; Schlemmer, Heinz-Peter; Ladd, Mark E.; Rieken, Stefan; Debus, Jürgen; et al.
Abstract: Ultra-high field MRI is an emerging technique promising high-resolution images for radiotherapy planning. We compared a 7 Tesla FLAIR sequence with clinical FLAIR imaging at 3 Tesla in glioblastoma patients before radiotherapy. High-resolution 7 Tesla FLAIR imaging may enhance the depiction of organs at risk and possibly modify target volumes.